2008
DOI: 10.1007/s10620-008-0483-8
|View full text |Cite
|
Sign up to set email alerts
|

Access to Treatment of Hepatitis C in Prison Inmates

Abstract: We conducted a prospective study to investigate access to treatment in hepatitis C in 268 prisoners. Hepatitis C positivity had been known for 182 prisoners previously and 19 reported previous attempts to treat (10%). In comparison, during our study, 86/268 prisoners (32%) started therapy (P < 0.0001). They represented 41% of 211 prisoners with a positive viral load. In the genotype 2 or 3 group, 46 prisoners (50%) started therapy versus 40 prisoners (33%) with other genotypes (P = 0.01). This difference was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Incarceration can provide a point of access for HIV/HCV services [1620], but this does not always translate to successful navigation of the care continuum [21–25]. Community supervision can provide another opportunity to facilitate access to HIV/HCV services, but this opportunity is often not realized [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Incarceration can provide a point of access for HIV/HCV services [1620], but this does not always translate to successful navigation of the care continuum [21–25]. Community supervision can provide another opportunity to facilitate access to HIV/HCV services, but this opportunity is often not realized [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…No comparison was made with the nonincarcerated population. Strock et al published a series of 268 prisoners that were known to be HCV positive 14. Treatment with Peg‐IFN‐α and RBV was offered to 86 patients and 52% achieved an SVR.…”
mentioning
confidence: 99%
“…Factors reported as potential obstacles to treatment of chronic HCV infection, especially in correctional populations [5,8,10], such as active drug substance abuse, psychiatric illness, length of treatment and poor adherence did not affect the end points of this study.…”
Section: Resultsmentioning
confidence: 84%
“…Studies in various correctional facilities have suggested that 59 to 85% of patients presenting with confirmed HCV infection go untreated; [8,10,12,13]. Recently Rice has reported a lower proportion (40%) of untreated patients [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation